Carbon layer supported nickel catalyst for sodium borohydride (NaBH4) dehydrogenation - Lee, Jaeyeong; Shin, Hojun; Choi, Kyoung Soon; Lee, Jouhahn; Choi, Jae Young; Yu, Hak Ki (International Journal of Hydrogen Energy, 2019)
In this paper, a nickel (Ni) catalyst with large surface area supported by a graphitic layer is proposed. The graphitic layer is formed on a Ni foil by chemical vapor deposition (CVD) using CH4 as a source. The Ni foil is partially etched by a chemical etchant to increase the surface to volume ratio. The H2 generation rates of the catalysts for different Ni etching times are measured and their surfaces are observed using an optical microscope. The optimized Ni etching time is 6 h, and the catalyst prepared by 6 h of etching shows an H2 generation rate of about 600 ml/min⋅(g metal). The 6-h etched Ni/graphitic layer (Ni/G) is reused five times to confirm durability; it shows a high performance without any degradation. The H2 generation rate for different concentrations of NaBH4 is measured. The reaction follows first order kinetics, which means that the higher the concentration of NaBH4 is, the faster the H2 generation is.
Keywords: Chemical vapor depositions (CVD); First order kinetics; Graphitic layers; NaBH4; Ni catalysts; Renewable energies; Supported nickel catalysts; Surface-to-volume ratio; Dehydrogenation; Graphitic layer; NaBH4; Ni catalyst; Renewable energy